An experimental investigation of bond and compressive strength of concrete with mineral admixtures at high temperatures - Tanyildizi, Harun; Coşkun, Ahmet; Somunkiran, Ilyas (King Fahd University of Petroleum and Minerals, 2008)
[Abstract Not Available]